Caracterização de núcleos de segurança do paciente em hospitais públicos estaduais do Espírito Santo - Coslop, Shaiane (2021)
Introduction The National Patient Safety Program was a milestone for Patient Safety in Brazil. When the program was launched, National Health Surveillance Agency established the guidelines for Health Services Establishments to promote the Patient Safety Program and mitigate adverse events. The actions included the mandatory creation of Patient Safety Centres. Objective: To describe the patient safety centers in public hospitals in the State of Espírito Santo. Methods: This is a descriptive study with a quantitative approach conducted on data provided by members of Patient Safety Centers of public hospitals in Espírito Santo, Brazil. The data was collected between November 2020 and January 2021 using a validated self-assessment tool that allows identifying processes and the structure of the Centers. In addition to that, data was collected about the participants and characteristics of each Center. Data was analyzed using Microsoft Excel. Results: Eight hospitals participated in the research, of which 62.5% are located in the metropolitan area. Most hospitals indicated having structured Centers, and 07 (87.5%) Centers reported having multidisciplinary teams. Problems with physical space (n = 1), internet access (n = 1) and printer (n = 1) were pointed out. Three (37.5%) participants characterized their Centers as having a predominance of fully implemented processes and three (37.5%) indicated partially implemented processes. ‘Patient Identification’ and ‘Hand Hygiene’ (87.5%) were the processes most indicated as implemented. The ‘Effective Communication’ process was implemented by one Center (12.5%) and the process to ‘Encourage patients and family members to get involved in their own safety’ by two (25.0%). Conclusion: Although the results indicate the existence of structured Centers in most of the hospitals, the lack of structure in some Centers can be considered a critical risk. Fragile processes were predominant in most Centers. The results identified guiding points to establish measures to improve existing Patient Safety Centers and guide their structuring in other hospitals. The results point to the existence of hospitals in the State that still do not achieve the requirements of the current legislation for the implementation of the National Patient Safety Program, suggesting the need to strengthen the safety culture within hospitals and greater discussion of the theme at the State level.